2022 18th International Conference on the European Energy Market (EEM) 2022
DOI: 10.1109/eem54602.2022.9921138
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility markets in the EU: Emerging approaches and new options for market design

Abstract: The Clean Energy Package aims to transit towards cleaner energy in the European Union and requires market reforms towards small-scale flexibility provision and the creation of local flexibility markets. However, the progress in many Member States is slow. While several Member States have initiated a reform of their existing energy market structures, only few have started the creation of local flexibility markets. This paper provides an overview of emerging flexibility markets in the EU. This paper also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…By doing so, citizens may actively participate in the energy system and foster new networks of local relations by sharing their surplus energy. Through ECs, consumers will also find it easier to invest in renewable energy, and then consume, store, or sell the energy that they produce, and even, in the near future, provide flexible services [2]. Several studies (e.g., [3][4][5]) have already shown that, through these investments, households can save on electricity bills by installing photovoltaic (PV) systems, recovering the full cost of their investment in a short period, and the focus is shifting even more to innovative business models and enabling sharing technologies [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, citizens may actively participate in the energy system and foster new networks of local relations by sharing their surplus energy. Through ECs, consumers will also find it easier to invest in renewable energy, and then consume, store, or sell the energy that they produce, and even, in the near future, provide flexible services [2]. Several studies (e.g., [3][4][5]) have already shown that, through these investments, households can save on electricity bills by installing photovoltaic (PV) systems, recovering the full cost of their investment in a short period, and the focus is shifting even more to innovative business models and enabling sharing technologies [4].…”
Section: Introductionmentioning
confidence: 99%
“…. 2 For ECs with the main business activity being the generation of energy, we used energy generated by their plants. For ECs with the main business activity being retail although owning shares in generation plants, we used the energy generated.…”
mentioning
confidence: 99%
“…Local energy market (LEM) [6] have also been introduced to improve the energy and economic efficiency at a local level. Some studies [7] compare the various designs respectively for tariff, LFM, etc. However, due to the complexity of the challenges which may vary under different conditions, it is not straightforward to determine the most suitable solution in a specific circumstance while the success potential of a solution highly depends on context.…”
Section: Introductionmentioning
confidence: 99%